A case of cognitive impairment in an ex-boxer - Hiroshi Yoshino; Hajime Takechi (Journal of Family Medicine and Primary Care)
Chronic traumatic encephalopathy (CTE) is a neurodegenerative disease related to the long-term consequences of repetitive cranial trauma. However, the CTE clinical phenotype has yet to be clearly defined. A 63-year-old man visited the hospital due to memory impairment. He was a former boxer. He scored 23 points on the Mini-Mental State Examination (MMSE). Magnetic resonance imaging (MRI) of the brain showed mild hippocampal atrophy. Reduced perfusion is identified in the bilateral frontal and parietotemporal lobes in cerebral blood flow on single photon emission computed tomography (SPECT). From detailed history taking, neuropsychological testing and neuroimaging, our case has not only suggestive probable CTE but also comorbid Alzheimer’s disease (AD). The diagnosis process of CTE is complex; therefore, detailed longitudinal history taking, neuropsychological testing and imaging were important.